Digital Storytelling: Enhancing the Inno-Life Tourism Community Prototype Identities Through the Power of the Community Innovators Storytellers - Chaiyasut, Khontaros; Wattanalaungarun, Worapol; Sa-ingthong , Kritch (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2025)
This article aims to extract the knowledge and wisdom of tourism communities to inform tourism community storytelling. Develop the potential of community innovators and storytellers and develop digital storytelling to convey community stories. The research methodology consisted of three phases, in accordance with the objectives. The sample included representatives of local wisdom scholars and representatives from the tourism communities of Ban Mae Kampong, Ban Pa Tan, and Ban Pong Kwao, Chiang Mai Province. The content included knowledge from local wisdom and tourism community identity. The research instrument used was a knowledge record form.The results revealed that the tourism communities of Ban Pa Tan, Ban Mae Kampong, and Ban Pong Kwao possess distinctive tourism community storytelling knowledge and diverse tourism expertise. The communities have developed their potential as innovative storytellers. The communities expressed the highest level of satisfaction with this development and wish for continued development projects. The communities are capable of conveying the stories of their three tourism villages: Ban Pa Tan, Ban Mae Kampong, and Ban Pong Kwao through digital storytelling media, including e-books, clips, and the website https://digitalstorytelling.lllskill.com. Add value to tourism, enhance the identity of tourism communities, and enhance the value of local resources through the process of promoting community identity. Communities share their stories, creating memorable experiences and immersing tourists in their communities